The effect of intercropping and different dose of goat manure application on growth of Pogestemon cablin Benth - Rivan Rinaldi; Indra Indra; Muhammad Syaifullah; Rina Sriwati; Bob Douma; Zulfahrizal Zulfahrizal; Ulfa Hansri Ar Rasyid (Journal of Patchouli and Essential Oil Products, 2022)
Patchouli (Pogostemon cablin Benth) is a perennial aromatic crop that can produceessential oil which is generally used as a mixture of ingredients for making cosmetics, pharmaceuticals, and aromatherapy which functions as a binder/fixative agent and pharmaceuticals. Although the production of patchouli increases year to year, the productivity per hectare of this plant showed a decreasing pattern. Efforts are needed to increase the productivity of patchouli, such as improving seeds quality and applying best management practices in planting. This study aimed to examine the optimum application of manure doses and intercropping practice on maximum growth of patchouli at first and two months after planting. The RCD (Randomize Complete Design) was conducted by using a cropping system and the application of goat manure in different doses. There were two levels of the cropping system: monocropping and intercropping with mung beans (Phaseolus radiatus) and four-level of manure in different doses were applied, 0 g, 500 g, 1000 g and 2000 g. ANOVA analysis shows that no interaction between cropping system and manure application on the growth of patchouli. All variables of patchouli growth in monocropping are better than in intercropping at two months after transplanting. Furthermore, there was no effect of manure application on canopy width, fresh and dry biomass of patchouli. The effect is only found on plant height and tree basal diameter, while without manure application and 500 g application is greater than 1000 g and 2000 g of manure application.